Power in Top Management Teams: Dimensions, Measurement, and Validation - Finkelstein, Sydney (Academy of Management Journal, 1992)
Top managers' power plays a key role in strategic decision making. However, although numerous scholars have recognized its importance, very few have attempted to measure the phenomenon. In this article, I present a set of dimensions measuring top managers' power and suggest a measurement methodology to facilitate empirical inquiry. Data from a group of 1,763 top managers in three industries were used to assess the validity and reliability of the power dimensions in three studies. Results demonstrate strong support for the proposed power dimensions.